Purification of phytotoxic metabolites from culture filtrate of Fusarium oxysporum f. sp. cubense gcv 01210 (race 1) - Nayanci Portal; Karlina García; Alitza Iglesias; Jenella Garraway; Barbarita Companioni; Luis Manuel Peña; Ramón Santos (Biotecnología Vegetal, 2011)
Panama disease, caused by Fusarium oxysporum f. sp. cubense, is considered a destructive disease of economic importance in the genus Musa. The culture filtrates of the pathogen have been used to differentiate cultivars, but have not been identified metabolites involved in the differential response. The aim of this study was to purify phytotoxic metabolites present in the culture filtrate of Fusarium oxysporum f. sp. cubense GCV [01210] Race 1 for further chemical characterization. We used a culture filtrate of 15 days of incubation. The phytotoxic activity was tested with a leaf bioassay on the susceptible cultivar ‘Gros Michel’ and resistant ‘FHIA 01’. The organic extract was extracted and fractionated. It was partitioned with organic solvents of rising polarity and found the complexity of each of the fractions by TLC. The metabolites were purified by flash column chromatography. Two compounds were purified from the culture filtrate of the pathogen which not only differed in color (blue and pale yellow), but also in polarity. Fractions B (containing blue compound) and E (containing yellow compound) produced significant differences in lesion area between resistant and susceptible cultivar. These results are not conclusive but, it is the basis for the identification of compounds involved in the differential response of Musa spp. cultivars to the culture filtrate of Fusarium oxysporum f. sp. cubense.